Adverse events in the nervous system associated with blinatumomab: a real-world study - Wen Gao; Jingwei Yu; Yifei Sun; Zheng Song; Xia Liu; Xue Han; Lanfan Li; Lihua Qiu; Shiyong Zhou; Zhengzi Qian; Xianhuo Wang; Huilai Zhang (BMC Medicine)
Abstract Background Nervous system toxicity (NST) is a frequent and serious adverse event (AE) associated with blinatumomab, the first bispecific antibody drug targeting CD19 and CD3. Real-world data are needed to better understand the incidence and characteristics of NST in clinical practice. Methods Data were obtained from the FDA Adverse Event Reporting System (FAERS). The reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence interval progressive neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) algorithms were utilized for data mining. Results A total of 5,962 blinatumomab-related cases were analyzed. NSTs were more frequent in males (44.01%) and younger individuals (18–45 years, 28.39%), with a higher prevalence in the USA (77.99%). Forty-three signals of NST were identified, of which neurotoxicity, neurological symptoms, agnosia, intention tremor, and immune effector cell-associated neurotoxicity syndrome had the highest ROR values. Concomitant use of medication for age, musculoskeletal system, genitourinary system, and sexual hormones were independent risk factors for NST, and age was an independent protective factor for fatal NST. The median time to onset (TTO) for neurological events was 3 days (range, 1 ~ 21). The highest fatality rate for neurological events was observed for increased intracranial pressure disorders, which also had the highest co-occurrence rate with cytokine release syndrome (CRS). Conclusions Age is an independent protective factor for fatal NST, and CRS leads to a higher fatality rate for NST patients treated with blinatumomab. Thorough medication evaluation should be conducted before administering blinatumomab, especially for high-risk patients with preexisting neurological conditions.